Reggio Emilia: An Essential Tool to Develop Critical Thinking in Early Childhood - Mercè Fernández Santín; Maria Feliu Torruella (Springer, 2017)
We seem to have a problem in arts education at pre-school level: the lack of specific training for teachers teaching this subject to very young children. The future preschool teachers' training seems to be focused on the teaching and learning aspects of artistic education however they receive little training on methodologies and philosophies. Therefore, when teachers have to face the classroom, the methodologies they use are usually quite traditional and do not favour the development of critical thinking skills in the students. There are different philosophies of arts education that might embed opportunities for reflection, art interpretation, experimentation, expression of emotions and feelings that if, in the case these philosophies, reach the classroom, may doubtlessly enrich the student's artistic training. Thus a conceptual framework based on one of these philosophies, named Reggio Emilia, arises. A systematic review of the literature which has been developed by categorising criteria from research papers and from examples of good practices. This categorisation might allow us to establish a framework that can be useful in the classrooms and can establish parameters of action that may have an impact on students, teachers and teachers' practice in general.